1997
DOI: 10.1111/j.1651-2227.1997.tb18357.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric disorders of childhood: Tourette's syndrome as a model

Abstract: Cohen DJ, Leckman JF, Pauls D. Neuropsychiatric disorders of childhood: Tourette's syndrome as a model. Acta Pzediatr 1997; Suppl422: 106-1 1. Stockholm. ISSN 0803-5326 Neuropsychiatric disorders of childhood include conditions such as autism, pervasive developmental disorder and attention deficit hyperactivity disorder. Tourette's syndrome (TS) of chronic, multiple, motor and vocal tics is a model neuropsychiatric disorder with a childhood onset and long-term, and sometimes life-long, course. Symptoms and sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 14 publications
0
7
1
Order By: Relevance
“…Basar and colleagues in a study showed that 30% of children with tethered spinal cord had Pollakiuria (19). Male dominance in Pollakiuria was seen in some studies leading to externalization of male genitalia (20)(21)(22), however, in the current study, there was an equal number of boys and girls. In some studies, certain medications, such as milnacipran and fluoxetine, may result in Pollakiuria (23,24).…”
Section: Discussioncontrasting
confidence: 54%
“…Basar and colleagues in a study showed that 30% of children with tethered spinal cord had Pollakiuria (19). Male dominance in Pollakiuria was seen in some studies leading to externalization of male genitalia (20)(21)(22), however, in the current study, there was an equal number of boys and girls. In some studies, certain medications, such as milnacipran and fluoxetine, may result in Pollakiuria (23,24).…”
Section: Discussioncontrasting
confidence: 54%
“…7,8 This has been postulated to be due variously to a TS gene-by-gender interaction, 1,33 an autoimmunity-bygender interaction, 34 or a hormone-by-gender interaction 35 (ie, tic facilitation in males, or tic suppression in females, by increasing levels of a gender-associated hormone during childhood, when TS symptoms usually begin). We've observed that male transgenic mice tic significantly more severely than do female transgenics in one measure-tic flurries-while likewise show-ing trends toward more tic complexity.…”
Section: Gender-specific Hormones May Aggravate Tic Severity In Male mentioning
confidence: 99%
“…(Bakker et al 2002) Tourette's syndrome (TS) is defined as Tourette's disorder in the DSM-IV-TR (American Psychiatric Association 2000). Cohen et al (1997) have presented TS as a model neuropsychiatric disorder. We would further qualify TS as a neuropsychiatric developmental disorder (NPDD).…”
Section: Introductionmentioning
confidence: 99%